ChemInform Abstract: N, N′‐Diamidocarbenes: Isolable Divalent Carbons with Bona Fide Carbene Reactivity. Issue 44 (13th October 2016) - Moerdyk, Jonathan P.; Schilter, David; Bielawski, Christopher W.
Abstract: Review: 75 refs.